2016
DOI: 10.1007/s10551-016-3219-2
|View full text |Cite
|
Sign up to set email alerts
|

Both Sides of the Coin: Motives for Corruption Among Public Officials and Business Employees

Abstract: The aim of this study is to better understand why public officials and business employees engage in corruption. Insight into individual-level explanations for corruption was obtained with the aid of a self-report survey. The results suggest that the most indicative factors of whether or not individuals are corruption-prone are as follows: the moral conviction they have to refrain from corruption; perceptions of whether their colleagues approve of and engage in corruption; and difficulties experienced in comply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 79 publications
5
83
1
3
Order By: Relevance
“…Importantly, the pattern of results was identical for public and private sector respondents when business employees were asked about their proneness to active bribery, and public officials about their proneness to passive bribery. This indicates that the same motives underlie both sides of bribery (Gorsira et al 2016). In the present study, we expect these individual motives to be related to public officials' and business employees' proneness to corruption.…”
Section: Individual Factors Explaining Corruptionmentioning
confidence: 75%
See 4 more Smart Citations
“…Importantly, the pattern of results was identical for public and private sector respondents when business employees were asked about their proneness to active bribery, and public officials about their proneness to passive bribery. This indicates that the same motives underlie both sides of bribery (Gorsira et al 2016). In the present study, we expect these individual motives to be related to public officials' and business employees' proneness to corruption.…”
Section: Individual Factors Explaining Corruptionmentioning
confidence: 75%
“…8 Nonetheless, the same survey indicates that more than half of the Dutch respondents think corruption is a widespread phenomenon in their country. Another study revealed that approximately 20% 9 of Dutch public officials reported having engaged in bribery-related behaviour in the past and/or to have an intention to do so in the near future (Gorsira et al 2016). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations